Contributions of the nursing team in the care of patients diagnosed with brain death admitted to the intensive care unit (Research, Society and Development, 2023)
The objective of this work is to characterize the attributions of nursing professionals regarding the care of patients diagnosed with brain death and regarding the process of donation and transplantation of organs and tissues. Method: Integrative review. Results. It is up to the Nurse to: Plan actions aimed at optimizing the donation and collection of organs and tissues for transplantation, with regard to the recipient, it is the responsibility of the nurse to provide all the nursing care inherent to this patient, to apply the SAE in all phases of the donation and transplant process, Identify the Nursing Diagnoses of risk, real and well-being of the receiver. Discussion: Transplantation is the only health treatment in which society can act effectively and the transplant sector is a sector that must work quickly and efficiently, as the time between retention and implementation are key factors for the survival, in most places, there is a certain protocol management of brain-dead patients and potential donors, these protocols, in addition to providing information about the tissue donation process itself, can deal with routines related to the donor's families. Conclusion: The main attributions of the nursing team to the potential donor patient are: monitoring the patient's hemodynamic condition, maintaining an elevated position, strict monitoring of vital signs, airway aspiration, measurement of central venous pressure, monitoring of fluid balance, collection of exams, diet infusions, monitoring of capillary blood glucose and administration of drug therapies.